PERAN GURU DALAM PEMBIASAAN POLA HIDUP SEHAT ANAK USIA 5-6 TAHUN DI ABC123 KOTA PONTIANAK - Harnum, Anggari Ludmilla; Aunurrahman, Aunurrahman; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the role of teachers in habituating healthy lifestyles of children aged 5-6 years in abc123 Pontianak. The research method used is descriptive with a form of qualitative research. The data source of this study are 2 teachers and childrens aged 5-6 years K2 class abc123. Research techniques using observation techniques with observation guides, interview techniques with interview guides anddocumentation techniques with documentaries. Analysis of research data is data reduction, data presentation, and drawing conclusions/verification. From the results of the study it was generally concluded that the teacher had played an active role, both as an inspirator, motivator, facilitator, and evaluator in the habit of living a healthy lifestyle. Specifically summarized as follows: As an inspirator the teacher gives instructions and role models, as a motivator the teacher motivates, supports and encourages the child, as a facilitator the teacher facilitates and provides various facilities, and as an evaluator the teacher observes, collects information and evaluates the process and results child learning. The advice given is so that the teacher canapply consistently and thoroughly for all childrens in the habit of living a healthy lifestyle.